2022
DOI: 10.55519/jamc-03-s1-9858
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Media on Ocular Trauma in Our Setup

Abstract: Background: Ocular injuries are one of the most common causes of monocular visual impairment and blindness worldwide. However, surveys done in only hospitals underestimate the incidence of oculars trauma. Aim of the study was to draw the attention towards significant increase in eye injuries amongst, or by, the children in few months in our setup following the start of airing of the drama series Ertughral Ghazi on television. It is the need of the day to plan safety strategies for prevention of ocular injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In our study clinical staff-related cancelation accounted for 11.9% of all canceled operations, and compared to other studies like Hawassa Specialized Hospital, Jimma University Hospital Hong Kong, Spain and India [27,36,43,[48][49][50], the cancelation due to clinical staff is acceptable in our study. The commonest reason from clinical staff is surgeon-related factors.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…In our study clinical staff-related cancelation accounted for 11.9% of all canceled operations, and compared to other studies like Hawassa Specialized Hospital, Jimma University Hospital Hong Kong, Spain and India [27,36,43,[48][49][50], the cancelation due to clinical staff is acceptable in our study. The commonest reason from clinical staff is surgeon-related factors.…”
supporting
confidence: 58%
“…A wide range of cancellation rates from 1% to 40% was reported in the literature depending on the study design, types of hospitals and their level and capacity, how cancelation is defined, types of patients and the medical specialties. Our data collection was prospective one on specially designed data collection sheets which were recorded daily and checked weekly by the principal investigator, which minimized the underscoring of cancellation [2,4,5,11,13,22,[34][35][36][37][38][39].…”
mentioning
confidence: 99%
“…It is not surprising that one of the toxic effects of heavy metals, in single or multi-metallic combination, is the alteration of metabolic profiles that lead to gut dysbiosis[ 82 ]. In a recent review, Zafar and Habib[ 83 ] found the following bacteria to be greatly decreased in the gastrointestinal tract of children with autism: Bacteroides, bifodobacterium, lactobacillus, and prevotella. In a separate review, Boonchooduang et al [ 81 ] found bifodobacterium and bacteroides to be the best candidates for analyses in stool samples of children and adolescents with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Other presentations, such as abdominal discomfort, nausea and vomiting are generally related to a high worm burden. However, extra-intestinal organ involvement has been reported, including liver, kidney, peritoneal cavity, uterus, ovaries, mesentery, and lymph nodes [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%